Pengembangan Penghidupan Berkelanjutan sebagai Upaya Peningkatan Ketahanan dan Kesejahteraan Nelayan Gillnet di Lampung Timur - David Julian; Muhammad Reza; Herman Yulianto (Pusat riset dan Inovasi Nasional, 2026)
Gillnet fisheries play an important role in supporting the local economy and the welfare of coastal communities. However, fishermen still face challenges related to unequal access to livelihood assets and high vulnerability to external factors such as seasonal changes, catch fluctuations, market pressures, and environmental conditions. This study aimed to analyze the level of vulnerability, identify livelihood assets, and formulate strategies for sustainable livelihood development among gillnet fishing communities. The study was conducted in Margasari and Muara Gading Mas Villages in September 2025 using a mixed-method approach, combining questionnaires, in-depth interviews, and field observations. Samples were selected through purposive sampling, and data were analyzed using descriptive quantitative and qualitative methods supported by a Likert scale. The results showed that fishermen’s vulnerability is relatively high (54.5%), affecting income stability. Social (81.4%) and natural (78.7%) assets are relatively strong, while human (38.6%), physic (48.3%), and financial (43.20%) assets remain relatively low. Limited education, lack of training, and restricted access to financial resources are the main constraints, leading to low adaptive capacity and limited livelihood diversification. Recommended strategies include improving human resource capacity, strengthening access to financial capital, and developing livelihood diversification based on local potential. These efforts are expected to enhance household economic resilience and support sustainable livelihoods among gillnet fishing communities.